Polychlorinated polymer / graphene oxide composite membrane for ammonia separation and preparation method of polychlorinated polymer / graphene oxide composite membrane
By loading carbon-carbon double bond-containing anicyclic compounds on the polychlorinated polymer/graphene oxide composite film and quaternization and metal chloride treatment, the problems of low ammonia selectivity and low ammonia permeability of the existing ammonia separation membrane were solved, and the ammonia separation effect with high efficiency and low energy consumption was achieved.
Patent Information
- Application Number
- CN202411863477.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-17
AI Technical Summary
The existing ammonia separation membranes have problems such as low ammonia selectivity and low ammonia permeability flux, making it difficult to achieve efficient and low energy consumption ammonia separation.
Using a composite polychlorinated polymer/graphene oxide film, a highly selective and highly permeable ammonia separation membrane was formed by loading a carbon-carbon double bond on the graphene oxide, and quaternization and metal chloride treatment.
Continuous, fast and low-energy separation of ammonia is achieved, with ammonia permeability up to 3586.3 Barrer, and ammonia/nitrogen and ammonia/hydrogen selectivity significantly improved.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of new chemical materials, and in particular to a polychlorinated polymer / graphene oxide composite membrane for ammonia separation and a preparation method thereof. Background Art
[0002] Ammonia (NH3) is an important chemical raw material, with an annual global production of more than 200 million tons. NH3 is widely used, including fertilizer manufacturing, pharmaceutical production, and refrigerant production. In recent years, with the greenhouse effect caused by the use of carbon energy, NH3 has gradually attracted the attention of researchers as a new energy source. NH3 can be pressurized and liquefied at room temperature, has a high energy density, is easy to store and transport, and can be used as automobile drive fuel and gas turbine power generation. On the other hand, excessive ammonia emissions into the atmosphere will cause serious environmental problems. The emitted NH3 reacts with acidic substances (such as SO x and NO x ) react to form ammonium salts, which form air particles. Therefore, it is of great significance to separate and recover ammonia-containing gases.
[0003] At present, the technologies for treating ammonia-containing gases mainly include absorption, adsorption, biological treatment and catalytic oxidation. The absorption method is the most commonly used method for treating ammonia-containing gases, and its process flow is relatively simple. However, the equipment of this method occupies a large area, the water consumption is also high, the steam consumption and energy consumption are large, and the wastewater generated may also cause secondary pollution. The adsorption method uses porous materials as adsorbents to adsorb NH3 onto the surface of the material, thereby achieving the separation of NH3. This method has the advantages of low energy consumption and high NH3 removal rate, but it also has the problems of high cost and possible secondary pollution, and is only suitable for treating gases with low NH3 concentrations. Common biological treatment methods include biofiltration, biotrickling and bioabsorption. Among them, the biofiltration technology is relatively mature and more widely used. It is suitable for treating gases with low NH3 concentrations, has the advantages of high efficiency and large processing capacity, and does not cause secondary pollution. However, when using this method to treat ammonia-containing gases, a large area is required, and the reaction conditions in the tower are difficult to control. In industry, NH3 is selectively decomposed into nitrogen (N2) and water (H2O) through catalytic oxidation. This method is applicable to the treatment of a variety of ammonia-containing gases and has a high treatment efficiency. However, the requirements for the catalyst are very stringent. The oxidizing property of the catalyst cannot be too high or too low. Too high oxidizing property will lead to the formation of byproducts such as nitrogen oxides, resulting in excessive emissions; while too low oxidizing property will reduce the reaction activity and it is difficult to meet the treatment standards.
[0004] Therefore, the development of green ammonia separation technology with high separation efficiency and low energy consumption is an important demand of the industry. Membrane separation technology has the characteristics of no phase change of components, green and environmentally friendly, low energy consumption and easy operation. The application of membrane separation technology in the treatment of ammonia-containing waste gas shows broad prospects. However, the existing ammonia separation membranes have problems such as low ammonia selectivity and low ammonia permeation flux. So far, ammonia separation membranes with both high performance and low cost are still a severe technical challenge. Summary of the invention
[0005] In view of the problems of low ammonia selectivity and low ammonia permeation flux in ammonia separation membranes in the prior art, the present invention provides a polychlorinated polymer / graphene oxide composite membrane for ammonia separation and a preparation method thereof. Graphene oxide is loaded on a porous polymer substrate, and a polymer membrane with high selective adsorption for ammonia is loaded on the graphene oxide to prepare a polymer / graphene oxide composite ammonia-hydrogen separation membrane, which can realize continuous, rapid and low-energy separation of ammonia.
[0006] The present invention adopts the following technical solution:
[0007] A method for preparing a polychlorinated polymer / graphene oxide composite membrane for ammonia separation, characterized in that it comprises the following steps:
[0008] S1, dissolving graphene oxide (GO) in solvent I, and depositing it on a porous polymer substrate through a vacuum filtration device to obtain a graphene oxide composite membrane;
[0009] S2, dissolving a nitrogen heterocyclic compound containing a carbon-carbon double bond, a crosslinking agent and an initiator in solvent II, spin coating the mixture on the graphene oxide composite film, and then heating the mixture for 2-8 hours, and repeating the process for 5-20 times to obtain a polymer / graphene oxide composite film;
[0010] S3, soaking the polymer / graphene oxide composite film in a halogenated hydrocarbon solution, and then drying to obtain a quaternized polymer / graphene oxide composite film;
[0011] S4. Immerse the quaternized graphene oxide polymer composite membrane in a metal chloride solution and then dry it to obtain a polychlorinated polymer / graphene oxide composite membrane.
[0012] In the step S1, the mass ratio of graphene oxide to solvent I is 1:(5000-10000).
[0013] In the step S1, the diameter of the graphene oxide sheet is 0.2-0.4 μm.
[0014] In the step S1, the porous polymer substrate is one of a polyethersulfone filter membrane, a nylon filter membrane, a polypropylene filter membrane, and a polytetrafluoroethylene filter membrane with a pore size less than 0.2 μm.
[0015] In the step S1, the solvent I is deionized water.
[0016] In the step S2, the nitrogen heterocyclic compound is one of 1-vinylimidazole, 2-methyl-1-vinylimidazole, 3-vinylpyridine, 4-vinylpyridine, and 2-isopropenylpyridine.
[0017] In the step S2, the cross-linking agent is one of N,N′-methylenebisacrylamide, acrylamide, methacrylamide, terephthalic acid, styrene, and β-methylstyrene.
[0018] In the step S2, the initiator is one of azobisisobutyronitrile, sodium sulfite and azobisisobutyronitrile.
[0019] In the step S2, the solvent II is one of deionized water, methanol, ethanol, and dimethyl sulfoxide.
[0020] In step S2, the mass ratio of the nitrogen heterocyclic compound, the crosslinking agent and the initiator is 1:(0.5-2):(0.2-1), and the mass volume ratio of the nitrogen heterocyclic compound and the solvent II is 1g:10ml.
[0021] The heating temperature in step S2 is 60-80°C.
[0022] The halogenated hydrocarbon in the halogenated hydrocarbon solution in step S3 is one of methyl iodide, methyl bromide, and vinyl bromide, and the solvent is one of deionized water, methanol, ethanol, and dimethyl sulfoxide, wherein the volume ratio of the halogenated hydrocarbon to the solvent is 1:(10-15).
[0023] In step S3, the soaking temperature is 40-80° C. and the soaking time is 6-24 hours.
[0024] In step S4, the metal chloride in the metal chloride solution is one of CoCl2, CaCl2, MgCl2, ZnCl2, NiCl2, SnCl2, CuCl2, MnCl2, and FeCl2, and the solvent is one of methanol, ethanol, and dimethyl sulfoxide, wherein the molar volume ratio of the metal chloride to the solvent is (1-2) mol:1000ml.
[0025] In step S4, the soaking temperature is 40-80° C. and the soaking time is 6-24 hours.
[0026] A polychlorinated polymer / graphene oxide composite membrane for ammonia separation prepared according to the preparation method.
[0027] Application of the polychlorinated polymer / graphene oxide composite membrane prepared according to the preparation method in ammonia-hydrogen separation.
[0028] Compared with the prior art, the technical solution of the present invention has the following advantages:
[0029] A. The present invention selects graphene oxide to be loaded on a porous polymer substrate. Graphene oxide has a high specific surface area and a layered structure, which can effectively improve the permeation flux of the membrane to ammonia, and it can significantly improve the strength and toughness of the membrane and improve the mechanical properties of the membrane. Nitrogen heterocyclic compounds containing carbon-carbon double bonds are subjected to free radical polymerization on graphene oxide composite membranes to form highly cross-linked polymer membranes, and the thickness of the polymer membrane can be effectively controlled by controlling the concentration of the precursor solution and the number of times of application. And the polymer / graphene oxide composite membrane is quaternized and treated with metal chlorides, and polychlorine is introduced as ammonia selective adsorption sites to improve the selectivity for ammonia. Through the synergistic effect of graphene oxide and polymer membrane, the high selectivity and high permeation flux of ammonia are promoted synchronously. According to the preparation method of the present invention, composite membranes are prepared and ammonia separation is carried out by membrane separation, which can realize continuous, rapid and low-energy separation of ammonia.
[0030] B. The composite membrane obtained by the present invention has a highly efficient ammonia separation effect. When separating ammonia-containing gas, the ammonia permeability is as high as 3586.3 Barrer, and the ammonia / nitrogen and ammonia / hydrogen selectivities are as high as 674.1 and 214.8, respectively.
[0031] C. The raw materials for preparing the composite membrane of the present invention are either commercially available or can be synthesized at low cost, thereby significantly reducing the cost of membrane preparation and facilitating its large-scale application. DETAILED DESCRIPTION
[0032] The present invention can be implemented in many different forms and should not be construed as being limited to the embodiments set forth herein. Instead, these embodiments are provided so that the present disclosure will be thorough and complete and will fully convey the concept of the present invention to those skilled in the art. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative work are within the scope of protection of the present invention.
[0033] Embodiment 1:
[0034] This embodiment provides a polychlorinated polymer / graphene oxide composite membrane for ammonia separation, and the preparation method thereof comprises the following steps:
[0035] S1. Weigh GO powder (0.05 g) and mix with 500 mL of deionized water, and ultrasonicate for 30 min to prepare a uniform and stable GO solution. Deposit 50 mL of GO solution on a polyethersulfone filter membrane by vacuum filtration, and vacuum dry at 60 ° C for 24 h to prepare a graphene oxide composite membrane.
[0036] S2, weigh 1-vinyl imidazole (0.0531mol, 5g), N, N'-methylenebisacrylamide (0.0349mol, 5g), azobisisobutyronitrile (0.0061mol, 1g) and add them to 50mL methanol, ultrasonicate for 30min to obtain a precursor solution. Place the graphene oxide composite film on a desktop sizing machine, drop 1mL of the precursor solution, rotate at 1000rpm for 30 seconds, and then place it in an oven at 60°C for 2h to allow the monomer to completely free radical polymerize. Repeat this polymerization process 5 times to obtain a polymer / graphene oxide composite film.
[0037] Weigh iodomethane (1 mL) and mix with 10 mL methanol, and ultrasonicate for 30 min to prepare a uniform and stable solution. Soak the polymer / graphene oxide composite film in the iodomethane methanol solution at 40 ° C for 24 h, and dry it in a vacuum oven at 80 ° C for 24 h to obtain a quaternized polymer / graphene oxide composite film.
[0038] CoCl2 (0.05 mol, 6.49 g) was weighed and mixed with 50 mL of methanol, and ultrasonicated for 30 min to prepare a uniform and stable solution. The quaternized polymer graphene oxide composite membrane was immersed in the CoCl2 methanol solution at 40 ° C for 24 h, and dried in a vacuum oven at 80 ° C for 24 h to obtain a polymer / graphene oxide composite separation membrane, which was recorded as membrane A.
[0039] A gas separation device was used to separate a mixed gas containing ammonia, nitrogen and hydrogen, and the permeabilities of the three gases were tested and the ammonia / nitrogen and ammonia / hydrogen selectivities were calculated. The results showed that the pure ammonia permeability of membrane A was 3586.3 Barrer, and the ammonia / nitrogen and ammonia / hydrogen selectivities were 674.1 and 214.8, respectively.
[0040] Comparative Example 1:
[0041] This embodiment provides a composite film, and the preparation method thereof comprises the following steps:
[0042] S1. Weigh GO powder (0.05 g) and mix with 500 mL of deionized water, and ultrasonicate for 30 min to prepare a uniform and stable GO solution. Deposit 50 mL of GO solution on a polyethersulfone filter membrane by vacuum filtration, and vacuum dry at 60 ° C for 24 h to prepare a graphene oxide composite membrane.
[0043] S2, weigh 1-vinylimidazole (0.0531mol, 5g), N, N'-methylenebisacrylamide (0.0349mol, 5g), azobisisobutyronitrile (0.0061mol, 1g) and add them to 50mL methanol, ultrasonicate for 30min to obtain a precursor solution. Place the graphene oxide composite film on a desktop sizing machine, drop 1mL of the precursor solution, rotate at 1000rpm for 30 seconds, and then place it in an oven at 60°C for 2h to allow the monomer to completely free radical polymerize. Repeat this polymerization process 5 times to obtain a polymer / graphene oxide composite film, recorded as 1-vinylimidazole / graphene oxide composite film.
[0044] A gas separation device was used to separate the mixed gas containing ammonia, nitrogen and hydrogen, and the permeability of the three was tested and the ammonia / nitrogen and ammonia / hydrogen selectivities were calculated. The results showed that the pure ammonia permeability of the 1-vinylimidazole / graphene oxide composite membrane was 790.6 Barrer, and the ammonia / nitrogen and ammonia / hydrogen selectivities were 398.5 and 69.3, respectively.
[0045] Combining Example 1 and Comparative Example 1, it can be seen that the composite membrane after quaternization and metal chloride treatment significantly improves the ammonia permeability and ammonia selectivity of the membrane, and the ammonia separation performance is enhanced.
[0046] Embodiment 2:
[0047] This embodiment provides a polychlorinated polymer / graphene oxide composite membrane for ammonia separation, and the preparation method thereof comprises the following steps:
[0048] S1. Weigh GO powder (0.05 g) and mix with 500 mL of deionized water, and ultrasonicate for 30 min to prepare a uniform and stable GO solution. Deposit 50 mL of GO solution on a polyethersulfone filter membrane by vacuum filtration, and vacuum dry at 60 ° C for 24 h to prepare a graphene oxide composite membrane.
[0049] S2, weigh 2-methyl-1-vinyl imidazole (0.052mol, 5g), N, N'-methylenebisacrylamide (0.0175mol, 2.5g), azobisisobutyronitrile (0.0061mol, 1g) and add them to 50mL methanol, ultrasonicate for 30min to obtain a precursor solution. Place the graphene oxide composite film on a desktop sizing machine, drop 1mL of the precursor solution, rotate at 1000rpm for 30 seconds, and then place it in an oven at 60°C for 3 hours to allow the monomer to completely free radical polymerize. Repeat this polymerization process 10 times to obtain a polymer / graphene oxide composite film.
[0050] S3, weigh iodomethane (1 mL) and mix with 10 mL methanol, and ultrasonicate for 30 min to prepare a uniform and stable solution. Soak the polymer / graphene oxide composite film in the iodomethane methanol solution at 40° C. for 24 h, and dry it in a vacuum oven at 80° C. for 24 h to obtain a quaternized polymer / graphene oxide composite film.
[0051] S4, weigh CoCl2 (0.05 mol, 6.49 g) and mix with 50 mL methanol, and ultrasonicate for 30 min to prepare a uniform and stable solution. The quaternized polymer graphene oxide composite membrane is immersed in the CoCl2 methanol solution at 40°C for 24 h, and dried in a vacuum oven at 80°C for 24 h to obtain a polymer / graphene oxide composite separation membrane, which is recorded as membrane B.
[0052] A gas separation device was used to separate a mixed gas containing ammonia, nitrogen and hydrogen, and the permeabilities of the three gases were tested and the ammonia / nitrogen and ammonia / hydrogen selectivities were calculated. The results showed that the pure ammonia permeability of membrane B was 2534.3 Barrer, and the ammonia / nitrogen and ammonia / hydrogen selectivities were 520.2 and 160.7, respectively.
[0053] Comparative Example 2:
[0054] This embodiment provides a composite film, and the preparation method thereof comprises the following steps:
[0055] S1. Weigh GO powder (0.05 g) and mix with 500 mL of deionized water, and ultrasonicate for 30 min to prepare a uniform and stable GO solution. Deposit 50 mL of GO solution on a polyethersulfone filter membrane by vacuum filtration, and vacuum dry at 60 ° C for 24 h to prepare a graphene oxide composite membrane.
[0056] S2, weigh 2-methyl-1-vinyl imidazole (0.052mol, 5g), N, N'-methylenebisacrylamide (0.0175mol, 2.5g), azobisisobutyronitrile (0.0061mol, 1g) and add them to 50mL methanol, ultrasonicate for 30min to obtain a precursor solution. Place the graphene oxide composite film on a desktop sizing machine, drop 1mL of the precursor solution, rotate at 1000rpm for 30 seconds, and then place it in an oven at 60°C for 3 hours to allow the monomer to completely free radical polymerize. Repeat this polymerization process 10 times to obtain a polymer / graphene oxide composite film.
[0057] S3. Weigh iodomethane (1 mL) and mix with 10 mL methanol, and ultrasonicate for 30 min to prepare a uniform and stable solution. Soak the polymer / graphene oxide composite film in the iodomethane methanol solution at 40° C. for 24 h, and dry it in a vacuum oven at 80° C. for 24 h to obtain a quaternized polymer / graphene oxide composite film, which is recorded as 2-methyl-1-vinylimidazole / graphene oxide composite film.
[0058] A gas separation device was used to separate the mixed gas containing ammonia, nitrogen and hydrogen, and the permeability of the three was tested and the ammonia / nitrogen and ammonia / hydrogen selectivities were calculated. The results showed that the pure ammonia permeability of the 2-methyl-1-vinylimidazole / graphene oxide composite membrane was 574.5 Barrer, and the ammonia / nitrogen and ammonia / hydrogen selectivities were 403.5 and 75.8, respectively.
[0059] Combining Example 2 and Comparative Example 2, it can be seen that the composite membrane after quaternization and metal chloride treatment significantly improves the ammonia permeability and ammonia selectivity of the membrane, and the ammonia separation performance is enhanced.
[0060] Embodiment 3:
[0061] This embodiment provides a polychlorinated polymer / graphene oxide composite membrane for ammonia separation, and the preparation method thereof comprises the following steps:
[0062] S1. Weigh GO powder (0.1 g) and mix with 500 mL of deionized water, and ultrasonicate for 30 min to prepare a uniform and stable GO solution. Deposit 50 mL of GO solution on a polyethersulfone filter membrane by vacuum filtration, and vacuum dry at 60 ° C for 24 h to prepare a graphene oxide composite membrane.
[0063] S2, weigh 3-vinylpyridine (0.047mol, 5g), acrylamide (0.0704mol, 7.5g), azobisisobutyronitrile (0.0061mol, 1g) and add them to 50mL methanol, ultrasonicate for 30min to obtain a precursor solution. Place the graphene oxide composite film on a desktop sizing machine, drop 1mL of the precursor solution, rotate at 1000rpm for 30 seconds, and then place it in an oven at 60°C for 4 hours to allow the monomer to completely free radical polymerize. Repeat this polymerization process 20 times to obtain a polymer / graphene oxide composite film.
[0064] S3, weigh iodomethane (1 mL) and mix with 10 mL methanol, and ultrasonicate for 30 min to prepare a uniform and stable solution. Soak the polymer / graphene oxide composite film in the iodomethane methanol solution at 50° C. for 12 h, and dry it in a vacuum oven at 80° C. for 24 h to obtain a quaternized polymer / graphene oxide composite film.
[0065] S4, weigh CoCl2 (0.05 mol, 6.49 g) and mix with 50 mL methanol, and ultrasonicate for 30 min to prepare a uniform and stable solution. The quaternized polymer graphene oxide composite membrane is immersed in the CoCl2 methanol solution at 60°C for 12 h, and dried in a vacuum oven at 80°C for 24 h to obtain a polymer / graphene oxide composite separation membrane, which is recorded as membrane C.
[0066] A gas separation device was used to separate a mixed gas containing ammonia, nitrogen and hydrogen, and the permeabilities of the three gases were tested and the ammonia / nitrogen and ammonia / hydrogen selectivities were calculated. The results showed that the pure ammonia permeability of membrane C was 2668.9 Barrer, and the ammonia / nitrogen and ammonia / hydrogen selectivities were 534.5 and 178.8, respectively.
[0067] Embodiment 4:
[0068] This embodiment provides a polychlorinated polymer / graphene oxide composite membrane for ammonia separation, and the preparation method thereof comprises the following steps:
[0069] S1. Weigh GO powder (0.05 g) and mix with 500 mL of deionized water, and ultrasonicate for 30 min to prepare a uniform and stable GO solution. Deposit 50 mL of GO solution on a polyethersulfone filter membrane by vacuum filtration, and vacuum dry at 60 ° C for 24 h to prepare a graphene oxide composite membrane.
[0070] S2, weigh 4-vinylpyridine (0.047mol, 5g), methacrylamide (0.0588mol, 10g), azobisisobutyronitrile (0.0305mol, 5g) and add them to 50mL methanol, ultrasonicate for 30min to obtain a precursor solution. Place the graphene oxide composite film on a desktop sizing machine, drop 1mL of the precursor solution, rotate at 1000rpm for 30 seconds, and then place it in an oven at 80°C for 6 hours to allow the monomer to completely free radical polymerize. Repeat this polymerization process 15 times to obtain a polymer / graphene oxide composite film.
[0071] S3, weigh iodomethane (1 mL) and mix with 10 mL methanol, and ultrasonicate for 30 min to prepare a uniform and stable solution. Soak the polymer / graphene oxide composite film in the iodomethane methanol solution at 40° C. for 24 h, and dry it in a vacuum oven at 80° C. for 24 h to obtain a quaternized polymer / graphene oxide composite film.
[0072] S4, weigh CoCl2 (0.05 mol, 6.49 g) and mix with 50 mL methanol, and ultrasonicate for 30 min to prepare a uniform and stable solution. Soak the quaternized polymer graphene oxide composite membrane in the CoCl2 methanol solution at 40°C for 24 h, and dry it in a vacuum oven at 60°C for 24 h to obtain a polymer / graphene oxide composite separation membrane, which is recorded as membrane D.
[0073] A gas separation device was used to separate a mixed gas containing ammonia, nitrogen and hydrogen, and the permeabilities of the three gases were tested and the ammonia / nitrogen and ammonia / hydrogen selectivities were calculated. The results showed that the pure ammonia permeability of membrane D was 1779.6 Barrer, and the ammonia / nitrogen and ammonia / hydrogen selectivities were 569.7 and 173.5, respectively.
[0074] Embodiment 5:
[0075] This embodiment provides a polychlorinated polymer / graphene oxide composite membrane for ammonia separation, and the preparation method thereof comprises the following steps:
[0076] S1. Weigh GO powder (0.1 g) and mix with 500 mL of deionized water, and ultrasonicate for 30 min to prepare a uniform and stable GO solution. Deposit 50 mL of GO solution on a polyethersulfone filter membrane by vacuum filtration, and vacuum dry at 60 ° C for 24 h to prepare a graphene oxide composite membrane.
[0077] S2, weigh 2-isopropenylpyridine (0.0335mol, 5g), styrene (0.048mol, 5g), azobisisobutyronitrile (0.0122mol, 2g) and add them to 50mL methanol, ultrasonicate for 30min to obtain a precursor solution. Place the graphene oxide composite film on a desktop sizing machine, drop 1mL of the precursor solution, rotate at 1000rpm for 30 seconds, and then place it in an oven at 60°C for 8 hours to allow the monomer to completely free radical polymerize. Repeat this polymerization process 5 times to obtain a polymer / graphene oxide composite film.
[0078] S3, weigh iodomethane (1 mL) and mix with 10 mL methanol, and ultrasonicate for 30 min to prepare a uniform and stable solution. Soak the polymer / graphene oxide composite film in the iodomethane methanol solution at 80° C. for 6 h, and dry it in a vacuum oven at 80° C. for 12 h to obtain a quaternized polymer / graphene oxide composite film.
[0079] S4, weigh CoCl2 (0.1 mol, 12.98 g) and mix with 50 mL methanol, and ultrasonicate for 30 min to prepare a uniform and stable solution. Soak the quaternized polymer graphene oxide composite membrane in the CoCl2 methanol solution at 40°C for 24 h, and dry it in a vacuum oven at 80°C for 24 h to obtain a polymer / graphene oxide composite separation membrane, which is recorded as membrane E.
[0080] A gas separation device was used to separate a mixed gas containing ammonia, nitrogen and hydrogen, and the permeabilities of the three gases were tested and the ammonia / nitrogen and ammonia / hydrogen selectivities were calculated. The results showed that the pure ammonia permeability of membrane E was 1779.6 Barrer, and the ammonia / nitrogen and ammonia / hydrogen selectivities were 569.7 and 173.5, respectively.
[0081] Embodiment 6:
[0082] This embodiment provides a polychlorinated polymer / graphene oxide composite membrane for ammonia separation, and the preparation method thereof comprises the following steps:
[0083] S1. Weigh GO powder (0.05 g) and mix with 500 mL of deionized water, and ultrasonicate for 30 min to prepare a uniform and stable GO solution. Deposit 50 mL of GO solution on a polyethersulfone filter membrane by vacuum filtration, and vacuum dry at 60 ° C for 24 h to prepare a graphene oxide composite membrane.
[0084] S2, weigh 1-vinyl imidazole (0.0531mol, 5g), terephthalic acid (0.0308mol, 5g), azobisisobutyronitrile (0.0183mol, 3g) and add them to 50mL methanol, ultrasonicate for 30min to obtain a precursor solution. Place the graphene oxide composite film on a desktop sizing machine, drop 1mL of the precursor solution, rotate at 1000rpm for 30 seconds, and then place it in an oven at 70°C for 5 hours to allow the monomer to completely free radical polymerize. Repeat this polymerization process 10 times to obtain a polymer / graphene oxide composite film.
[0085] S3, weigh iodomethane (1 mL) and mix with 15 mL methanol, and ultrasonicate for 30 min to prepare a uniform and stable solution. Soak the polymer / graphene oxide composite film in the iodomethane methanol solution at 40° C. for 24 h, and dry it in a vacuum oven at 60° C. for 24 h to obtain a quaternized polymer / graphene oxide composite film.
[0086] S4, weigh CoCl2 (0.05 mol, 6.49 g) and mix with 50 mL methanol, and ultrasonicate for 30 min to prepare a uniform and stable solution. The quaternized polymer graphene oxide composite membrane was immersed in the CoCl2 methanol solution at 80°C for 6 h, and dried in a vacuum oven at 80°C for 12 h to obtain a polymer / graphene oxide composite separation membrane, which was recorded as membrane F.
[0087] A gas separation device was used to separate a mixed gas containing ammonia, nitrogen and hydrogen, and the permeabilities of the three gases were tested and the ammonia / nitrogen and ammonia / hydrogen selectivities were calculated. The results showed that the pure ammonia permeability of membrane F was 1369.4 Barrer, and the ammonia / nitrogen and ammonia / hydrogen selectivities were 423.9 and 85.6, respectively.
[0088] Embodiment 7:
[0089] The composite membrane was prepared by a method similar to that of Example 1, except that the initiator was changed to azobisisobutyronitrile (0.0244 mol, 4 g) and the solvent was changed to ethanol to obtain similar results.
[0090] Embodiment 8:
[0091] The composite membrane was prepared by a method similar to that of Example 2, except that the initiator was changed to azobisisobutyronitrile (0.0305 mol, 5 g), the solvent was changed to deionized water, and the immersion temperature was changed to 50° C. to obtain similar results.
[0092] Embodiment 9:
[0093] The composite membrane was prepared by a method similar to that of Example 3, except that the porous polymer substrate was replaced by a nylon filter membrane, the immersion temperature was changed to 50° C., and the immersion time was changed to 12 h to obtain similar results.
[0094] Embodiment 10:
[0095] The composite membrane was prepared by a method similar to that of Example 4, except that the porous polymer substrate was replaced by a polypropylene filter membrane and the solvent was replaced by deionized water to obtain similar results.
[0096] Embodiment 11:
[0097] A composite membrane was prepared by a method similar to that of Example 6, except that the porous polymer substrate was replaced by a polytetrafluoroethylene filter membrane and the immersion time was changed to 12 h to obtain similar results.
[0098] Embodiment 12:
[0099] A composite membrane was prepared by a method similar to that of Example 1, except that the porous polymer substrate was replaced by a polytetrafluoroethylene filter membrane, the initiator was replaced by sodium sulfite (0.0079 mol, 1 g), and the immersion time was changed to 10 h to obtain similar results.
[0100] Embodiment 13:
[0101] The composite membrane was prepared by a method similar to that of Example 5, except that the porous polymer substrate was changed to a polypropylene filter membrane, the initiator was changed to azodicarbonamide (0.0119 mol, 1 g), and the immersion temperature was changed to 70° C. to obtain similar results.
[0102] Embodiment 14:
[0103] The composite membrane was prepared by a method similar to that of Example 1, except that the halogenated hydrocarbon was replaced by methyl bromide, and similar results were obtained.
[0104] Embodiment 15:
[0105] The composite membrane was prepared by a method similar to that of Example 1, except that the halogenated hydrocarbon was replaced by methyl bromide and the metal chloride was replaced by FeCl2 (0.05 mol, 6.3375 g), and similar results were obtained.
[0106] Embodiment 16:
[0107] A composite membrane was prepared by a method similar to that of Example 2, except that the halogenated hydrocarbon was replaced by vinyl bromide and the metal chloride was replaced by FeCl2 (0.05 mol, 6.3375 g), and similar results were obtained.
[0108] Embodiment 17:
[0109] A composite membrane was prepared by a method similar to that of Example 5, except that the porous polymer substrate was replaced by a polytetrafluoroethylene filter membrane, the halogenated hydrocarbon was replaced by vinyl bromide, and the metal chloride was replaced by FeCl2 (0.05 mol, 6.3375 g), and similar results were obtained.
[0110] Embodiment 18:
[0111] The composite membrane was prepared by a method similar to that of Example 3, except that the metal chloride was replaced by MgCl2 (0.05 mol, 4.76 g) to obtain similar results.
[0112] Embodiment 19:
[0113] A composite membrane was prepared by a method similar to that of Example 6, except that the porous polymer substrate was replaced by a polypropylene filter membrane, the initiator was replaced by azodicarbonamide (0.0119 mol, 1 g), and the metal chloride was replaced by MnCl2 (0.05 mol, 6.2920 g) to obtain similar results.
[0114] Embodiment 20:
[0115] A composite membrane was prepared by a method similar to that of Example 1, except that the porous polymer substrate was replaced by a nylon filter membrane, the initiator was replaced by azodicarbonamide (0.0119 mol, 1 g), and the metal chloride was replaced by ZnCl2 (0.05 mol, 6.8143 g), and similar results were obtained.
[0116] The present invention selects graphene oxide to be loaded on a porous polymer substrate. Graphene oxide has a high specific surface area and a layered structure, which can effectively improve the permeation flux of the membrane to ammonia, and it can significantly improve the strength and toughness of the membrane, and improve the mechanical properties of the membrane. Nitrogen heterocyclic compounds containing carbon-carbon double bonds are subjected to free radical polymerization on graphene oxide composite membranes to form highly cross-linked polymer membranes, and the thickness of the polymer membrane can be effectively controlled by controlling the concentration of the precursor solution and the number of times of application. And the polymer / graphene oxide composite membrane is quaternized and treated with metal chlorides, and polychlorine is introduced as ammonia selective adsorption sites to improve the selectivity for ammonia. Through the synergistic effect of graphene oxide and polymer membrane, the high selectivity and high permeation flux of ammonia are synchronously promoted. According to the preparation method of the present invention, composite membranes are prepared and ammonia separation is performed by membrane separation, and continuous, rapid and low-energy separation of ammonia can be achieved.
[0117] The raw materials for preparing the composite membrane of the present invention are either commercially available or can be synthesized at low cost, thereby significantly reducing the cost of membrane preparation and facilitating its large-scale application.
[0118] Anything not described in the present invention is applicable to the prior art.
[0119] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. However, the obvious changes or modifications derived therefrom are still within the scope of protection of the present invention.
Claims
1. A method for preparing a polychlorinated polymer / graphene oxide composite membrane for ammonia separation, characterized in that: The steps include: S1, dissolving graphene oxide (GO) in solvent I, and depositing it on a porous polymer substrate through a vacuum filtration device to obtain a graphene oxide composite membrane; S2, dissolving a nitrogen heterocyclic compound containing a carbon-carbon double bond, a crosslinking agent and an initiator in solvent II, spin coating the mixture on the graphene oxide composite film, and then heating the mixture for 2-8 hours, and repeating the process for 5-20 times to obtain a polymer / graphene oxide composite film; S3, soaking the polymer / graphene oxide composite film in a halogenated hydrocarbon solution, and then drying to obtain a quaternized polymer / graphene oxide composite film; S4. Immerse the quaternized graphene oxide polymer composite membrane in a metal chloride solution and then dry it to obtain a polychlorinated polymer / graphene oxide composite membrane.
2. The preparation method according to claim 1, characterized in that: In the step S1, the mass ratio of graphene oxide to solvent I is 1:(5000-10000).
3. The preparation method according to claim 1, characterized in that: In the step S1, the diameter of the graphene oxide sheet is 0.2-0.4 μm; The porous polymer substrate is one of a polyethersulfone filter membrane, a nylon filter membrane, a polypropylene filter membrane, and a polytetrafluoroethylene filter membrane having a pore size less than 0.2 μm; The solvent I is deionized water.
4. The preparation method according to claim 1, characterized in that: In step S2, the nitrogen heterocyclic compound is one of 1-vinylimidazole, 2-methyl-1-vinylimidazole, 3-vinylpyridine, 4-vinylpyridine, and 2-isopropenylpyridine; The cross-linking agent is one of N,N′-methylenebisacrylamide, acrylamide, methacrylamide, terephthalic acid, styrene, and β-methylstyrene; The initiator is one of azobisisobutyronitrile, sodium sulfite and azobisisobutyronitrile; The solvent II is one of deionized water, methanol, ethanol and dimethyl sulfoxide.
5. The preparation method according to claim 1, characterized in that: In step S2, the mass ratio of the nitrogen heterocyclic compound, the crosslinking agent and the initiator is 1:(0.5-2):(0.2-1), and the mass volume ratio of the nitrogen heterocyclic compound and the solvent II is 1g:10ml.
6. The preparation method according to claim 1, characterized in that: The heating temperature in step S2 is 60-80°C.
7. The preparation method according to claim 1, characterized in that: The halogenated hydrocarbon in the halogenated hydrocarbon solution in step S3 is one of methyl iodide, methyl bromide, and vinyl bromide, and the solvent is one of deionized water, methanol, ethanol, and dimethyl sulfoxide, wherein the volume ratio of the halogenated hydrocarbon to the solvent is 1:(10-15).
8. The preparation method according to claim 1, characterized in that: In step S3, the soaking temperature is 40-80° C., and the soaking time is 6-24 hours; the drying temperature is 60-80° C., and the drying time is 12-24 hours.
9. The preparation method according to claim 1, characterized in that: In step S4, the metal chloride in the metal chloride solution is one of CoCl2, CaCl2, MgCl2, ZnCl2, NiCl2, SnCl2, CuCl2, MnCl2, and FeCl2, and the solvent is one of methanol, ethanol, and dimethyl sulfoxide, wherein the molar volume ratio of the metal chloride to the solvent is (1-2) mol:1000ml.
10. The preparation method according to claim 1, characterized in that: In step S4, the soaking temperature is 40-80° C., and the soaking time is 6-24 hours; the drying temperature is 60-80° C., and the drying time is 12-24 hours.
11. A polychlorinated polymer / graphene oxide composite membrane for ammonia separation prepared by the preparation method according to any one of claims 1 to 10.
12. Use of a polychlorinated polymer / graphene oxide composite membrane prepared by the preparation method according to any one of claims 1 to 10 in ammonia-hydrogen separation.
Citation Information
Patent Citations
Anti-pollution composite graphene oxide nanofiltration membrane and production method thereof
CN106861465A
Preparation method of graphene oxide nanofiltration membrane with adjustable flux
CN108786464A
Polymer-based ammonia gas adsorbent and preparation method thereof
CN117920156A
Ammonia separation membrane filled with pores with double functional sites and preparation method of ammonia separation membrane
CN119034502A
Natural shampoo with the fuction of hair loss prevention and improving the condition of scalp by removing dead skin and manufacturing method thereof
KR1020240007816A